(untitled) (Andamios, Revista de Investigación Social, 2025)
This essay addresses the relevance of Mapuzungun, Ngutramkam, and the Mapuche oral mentality as part of everyday life. In this sense, the categories of experience and training are proposed from Latin American philosophy in authors such as Kusch, Fornet-Betancourt, and Dussel, to situate Mapuche orality in its epistemological contribution. Subsequently, Mapuzungun (the mapuche language) is presented in authors such as Catriquir (2007); Mariman (2009); Quidel (2013); Teillier, Llanquinao, and Salamanca (2018); Loncón (2019); Ñanculef and Cayupán (2016); and Ngutramkam (knowing how to converse) in Yanai (2008), elements of orality that, from Latin American philosophy, are interpreted as a rethinking of our colonized world. Likewise, the utilitarian knowledge of Modernity is criticized and the epistemological contribution of the Mapuche oral mentality, with its polyphony is emphasized, since it contributes far from the fragmentation of knowledge, enabling, through memory, images, words, and episteme, when the colonized world closes off other possibilities for happiness and life in decolonization.